2020
DOI: 10.1021/acsnano.0c02026
|View full text |Cite
|
Sign up to set email alerts
|

Helical Magnetic Field-Induced Real-Time Plasmonic Chirality Modulation

Abstract: The astrophysical phenomenon of mimetic helical magnetic field (h B)-assisted self-assembly is herein introduced to build helical superstructures that display chiroptical properties. As a building block, magnetoplasmonic (MagPlas) Ag@Fe3O4 core–shell nanoparticles are used to guide plasmonic Ag nanoparticles onto a helical magnetic flux. The chirality of the assembled helical structures and tailored circular dichroism are successfully tuned in real time, and the handedness of the assembled structures is dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 42 publications
1
86
0
1
Order By: Relevance
“…214 Another example makes use of a helical magnetic field to assemble magnetoplasmonic Ag@Fe 3 O 4 core-shell nanoparticles into chains stacked in a chiral nematic-like superstructure that can be dynamically modulated at the millisecond time scale. 215 Chirality can also be obtained by stacking layers of in-plane oriented 1D nano-objects or 1D assemblies with a twist, leading to so-called Bouligand structures. Using a very elegant and simple approach, Probst et al have recently shown that twisted chiral assemblies can be prepared from spherical gold nanoparticles (Fig.…”
Section: Materials Advancesmentioning
confidence: 99%
“…214 Another example makes use of a helical magnetic field to assemble magnetoplasmonic Ag@Fe 3 O 4 core-shell nanoparticles into chains stacked in a chiral nematic-like superstructure that can be dynamically modulated at the millisecond time scale. 215 Chirality can also be obtained by stacking layers of in-plane oriented 1D nano-objects or 1D assemblies with a twist, leading to so-called Bouligand structures. Using a very elegant and simple approach, Probst et al have recently shown that twisted chiral assemblies can be prepared from spherical gold nanoparticles (Fig.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Displayed colors can be dynamically tuned using helical magnetic field (hB), which was applied to dynamically transfer electromagnetic chirality to magnetoplasmonic Ag@Fe 3 O 4 NPs through the dynamic formation of helical superassemblies. [24] The helical superassemblies show engineerable CD signals as a function of the field strength and frequency of hB, to obtain full-color tuning capability with no need of a color filter. As a result, the hB-induced dynamic chirality transfer paves the way toward producing thin display panel with high light efficiency.…”
Section: Displaymentioning
confidence: 99%
“…[5] Chiral driving forces are indispensably applied to impose chirality onto inorganic NPs, which have been reviewed previously. [6][7][8] Chiral driving forces include chirality transfer from chiral ligands, [9][10][11] chiral templates [12] (such as DNA, [13] proteins, [14] peptides, [15] cellulose nanocrystals, [16] liquid crystals modified with chiral ligands, [17] lipidic nanoribbons, [18] chiral mesoporous silica, [19] nanohelices [20,21] ), circularly polarized light (CPL), [22] spatially chiral arrangement using lithography techniques, [23] helical magnetic fields, [24] orbital angular momentum, [25] macroscopic asymmetric gradients of biaxial strain fields, [26] and macroscopic shear forces. [27,28] A pair of chiral objects are designated as enantiomorphs, and especially a pair of chiral molecules are called enantiomers.…”
mentioning
confidence: 99%
“…Indeed, the phenomenon of helical magnetic field ( h B )‐driven symmetry breaking of light was used to induce self‐assembly of magnetoplasmonic Ag@Fe 3 O 4 core‐shell NPs (diameter of the Ag core is ~61.4 nm and the Fe 3 O 4 shell thickness is ~54.3 nm.) (Figure 13A) into helical superstructures with tailored, tunable, and switchable chiroptical properties in real‐time 156 . In Ag@Fe 3 O 4 NPs, Fe 3 O 4 magnetic shell was used to guide plasmonic materials onto the magnetic flux.…”
Section: Chemical Processes Used In Engineering Of Chiral Nanostructuresmentioning
confidence: 99%
“…Adapted with permission from Ref. 156 Copyright © 2020 American Chemical Society. (E) chiral colloidal clusters assembled from asymmetric dimers under alternating current electric fields (peak‐to‐peak voltage V pp = 11 V and ω = 600 Hz): (1) large field of view of chiral tetramers.…”
Section: Chemical Processes Used In Engineering Of Chiral Nanostructuresmentioning
confidence: 99%